Joint Belgium-Japan search for Antarctic meteorites in the 2010–2011 field season - Kaiden, Hiroshi; Goderis, Steven; Debaille, Vinciane; Kojima, Hedeyasu; Claeys, Philippe (2011)
info:eu-repo/semantics/published